An evaluation of the integration of the 'white' town of Pietersburg and the 'black' township of Seshego after the local government elections of 1995 - Mabotja, Mpheta Samuel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2001.